(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the question of the formation and development of the gazelle genre in the Turkic literature is revealed. The original samples of the Turkic gazelle on the material of Rabguzi’s lyrics, Kharezmi are analyzed. The author analyses the fragments from the works of Safi Serayi "Gulistan Bit Turks", too.